Tindak Tutur Direktif Pada Serial Nussa Season 2 Di Kanal Youtube Nussa Official - Suci Rahayu (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study aims to describe the form of directive speech acts in Serial Nussa Season 2. This type of research is descriptive qualitative. The research data, namely the character dialogues in the Nussa Season 2 Serial. The data source is on the Nussa Official Youtube Channel. Data collection was carried out by listening, noting, and classifying methods. The research instrument is an observation instrument by directly observing the research object, in this case the researcher uses all five senses, namely sight, hearing, smell, touch, and taste to obtain data. This instrument can be in the form of data cards, video recordings. Data analysis is carried out using the matching technique. Presenting the results of the analysis in a formal and informal manner. The results of the study show that there are 6 types of directive speech acts, namely requests, advice, orders, questions, prohibitions, and agreements. The category of direct literal questions dominates and from each category of directive speech acts in this case the speech acts of direct literal agreement are the least and only one data is found in the Nussa Season 2 series.